KORELASI ASPEK KOGNITIF TERHADAP KEPATUHAN MENGKONSUMSI TABLET FE PADA IBU HAMIL - Yanti, Lilis Candra; Widya, Wastu; Kristina, Yunita; Sulistyowati, Endang (Ensiklopedia of Journal, 2025)
Abstract: Pregnancy is a crucial phase in the human life cycle, especially because it is included in the golden period of the First 1,000 Days of Life (HPK), which starts from conception until the child is two years old. During pregnancy, the body's need for iron increases significantly, putting pregnant women at risk of anemia. The purpose of the study was to determine the correlation of cognitive aspects with adherence to taking Fe tablets in pregnant women. The research design used in this study was cross sectional. The research was conducted in the working area of Pasir Jaya Health Center. The research was conducted in September 2024. The population is all pregnant women who live in the Pasir Jaya Health Center working area, totaling 216 people. The sample amounted to 77 respondents.  The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed a relationship between (p value: 0.042) and perceptions (p value: 0.032) on compliance with Fe tablet consumption in pregnant women. Pregnant women are advised to follow the doctor's or midwife's recommendations regarding regular consumption of blood supplement tablets and not to skip doses.Keywords: Compliance, Knowledge, Perception.